Formation of a superstructure in 1T-TiSe2 induced at room temperature by electron beam irradiation. (18th July 2018) - Kobayashi, Keita; Yasuda, Hidehiro
Abstract: The formation of an unknown superstructure with a 2 a  × 2 a (where a is the lattice constant of the normal phase of 1 T -TiSe2 ) long period in multilayer 1 T -TiSe2 with a thickness of approximately 200 nm is induced at 296 K by electron beam irradiation during transmission electron microscopy (TEM). Since this superstructure remains unchanged even at 673 K, its formation mechanism cannot be explained by the known charge density wave phase transition of 1 T -TiSe2 . Electron energy loss and energy-dispersive x-ray spectroscopy indicate that the formation of the superstructure also cannot be attributed to chemical reaction with the ambient atmosphere. Based on scanning TEM, the superstructure is considered to be formed by the periodic distortion of the Ti atomic position in multilayer 1 T -TiSe2 due to the electron beam irradiation.